A methodology to develop collaborative robotic cyber physical systems for production environments - Azfar Khalid; Pierre Kirisci; Zied Ghrairi; Klaus-Dieter Thoben; Jürgen Pannek (Logistics Research, 2016)
The paper identifies the need for human robot collaboration for conventional light weight and heavy payload robots in future manufacturing environment. An overview of state of the art for these types of robots shows that there exists no solution for human robot collaboration. Here, we consider cyber physical systems, which are based on human worker participation as an integrated role in addition to its basic components. First, the paper identifies the collaborative schemes and a formal grading system is formulated based on four performance indicators. A detailed sensor catalog is established for one of the collaboration schemes, and performance indices are computed with various sensors. This study reveals an assessment of best and worst possible ranges of performance indices that are useful in the categorization of collaboration levels. To illustrate a possible solution, a hypothetical industrial scenario is discussed in a production environment. Generalizing this approach, a design methodology is developed for such human robot collaborative environments for various industrial scenarios to enable solution implementation.
Keywords: 650; Cyber physical system; Human robot collaboration; Collaborative robotics